Probing the structure and energetics of dislocation cores in sige alloys through Monte Carlo simulations - Remediakis, Ioannis N.; Jesson, David E.; Kelires, Pantelis C. (My University, 2006)
We present a methodology for the investigation of dislocation energetics in segregated alloys based on Monte Carlo simulations which equilibrate the topology and composition of the dislocation core and its surroundings. An environment-dependent partitioning of the system total energy into atomic contributions allows us to link the atomistic picture to continuum elasticity theory. The method is applied to extract core energies and radii of 60° glide dislocations in segregated SiGe alloys which are inaccessible by other methods.
Keywords: Computer simulation; Continuum mechanics; Germanium alloys; Topology; Silicon alloys